METAPHOR OF COSMOS–AS–POLIS IN THE STOIC TEACHING AND ITS ETHICAL AND COMMUNICATIVE CONSEQUENCES - F. B. Shcherbakov (Концепт: философия, религия, культура, 2019)
This article is considering origins of Stoic representation of Cosmos as The Universe State and there is briefly tracing its totemistic preconditions, which were proceeding from the primitive mythopoetic thinking’s specifics. Furthermore, there is proving a thesis about that the metaphor of Cosmos-Polis has emerged from searchings of an adequate philosophical language by early Greek thinkers, and that sociomorphical code was one of the most important metaphorical models of Cosmos in ancient philosophical poetics, not only for Stoics. A great number of political doctrines by Plato and faraway in the postplatonic tradition, including Stoa, were arising on the fundament of the this code. There is considering character of some Stoic ethical contradictions and is offering an attempt of resolving them through allocation of horizontically-civil and vertically-divine links in the Stoic teaching, which were containing peculiar dual system of communication of stoic sage with Cosmos.